Study of Scientific Aptitude and Academic Performance among Senior Secondary Science Students of Haryana State - Kusum, (JOURNAL OF INDIAN EDUCATION, 2023)
The present study was undertaken to analyse the scientific aptitude and academic performance of senior secondary science students of Haryana state with respect to school, gender, stream and coaching. The present study also inspected the influence of scientific aptitude on academic performance of senior secondary science students. Total sample of 400 students was selected at random from twenty government and twenty private schools of Haryana state. The tool used for measuring the level of scientific aptitude was Adolescents’ Scientific Aptitude Test (ASAT) developed and standardised by Kusum, Satish Kumar and Sumitra Devi (2021). Academic performance was assessed through marks obtained by senior secondary students in 12th board exam. The result of data analysis concluded that school and coaching significantly influenced the scientific aptitude, but gender and stream does not influence the scientific aptitude. Private school students and students taking coaching have more scientific aptitude. Result also revealed that the school, gender and coaching significantly influenced the academic performance but stream does not influence the academic performance. Significant and positive correlation of between academic performance and scientific aptitude was observed. The result revealed that 28 per cent of academic performance is determined and influenced by scientific aptitude.